(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The possibility of using immobilized organic reagents oxyazobirims and polyoxyflavones in the determination of aluminum, gallium, indium and tin ions by sorption-fluorescence method was studied. The optimal conditions for complex formation of these reagents with the studied metals were selected. The chemistry and spectral properties of chemical reactions were studied. Detection capabilities in solution and immobilized states were compared.